2020
DOI: 10.1177/1078155220955211
|View full text |Cite
|
Sign up to set email alerts
|

Awareness is the first step: What Ghanaian community pharmacists know about cancer

Abstract: Objectives The goal of this study was to access the knowledge of a representative sample of community pharmacists in Ghana on general cancer, risk factors, signs and symptom and most common cancer counseling points known to community pharmacists. Methods A structured online questionnaire was administered to 435 registered community pharmacists in the sixteen regions of Ghana. Key findings: Mean score for knowledge of cancer among community pharmacists was 6.8 ± 1.61 points out of a maximum score of 15 points, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 31 publications
3
19
2
Order By: Relevance
“…This finding might indicate a high level of awareness of the direct effect of modifiable lifestyle riskfactors on the development of certain types of cancer. Previous studies found similar research results(Mensah et al, 2021;Calvert et al, 2021).The study result showed that the female gender had less awareness than the male gender regarding the cancer risk. This result contrasts with results from a previous study, which found that the female gender had more awareness regarding cancer than the male gender (Al-Azri et al, 2021).…”
supporting
confidence: 76%
“…This finding might indicate a high level of awareness of the direct effect of modifiable lifestyle riskfactors on the development of certain types of cancer. Previous studies found similar research results(Mensah et al, 2021;Calvert et al, 2021).The study result showed that the female gender had less awareness than the male gender regarding the cancer risk. This result contrasts with results from a previous study, which found that the female gender had more awareness regarding cancer than the male gender (Al-Azri et al, 2021).…”
supporting
confidence: 76%
“…The anticancer mechanism of IOPS mainly includes: Decreasing the expression of MMP-2, MMP-7, and MMP-9, increasing the expression of tissue metallopeptidase inhibitor 2 (TIMP-2), and decreasing the expression of NF-κB in cancer cells [2,3,8,9,[84][85][86][87][88][89][90][91].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…The questionnaire for the study was extracted from previous or pre-test studies that evaluated community pharmacists in Ghana's knowledge of cancer, signs and symptoms, risk factors and cancer screening test. 13 A purposive sample of ten community pharmacists who pre-tested the previous study were used to test the post-test questionnaire after the educational intervention. A correlation test and retest scores 4 months later was 0.81.…”
Section: Survey Materialsmentioning
confidence: 99%
“…As part of the recommendation, a contextualized online continuous professional education on cancer was organized for community pharmacists who took part in the previous or pre-test study. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation